Retreatment with a flow diverter for recurrent blood blister-like aneurysms after embolization: A single-center case series - Yan, Yazhou; Zhu, Shijie; Yao, Hao; Wu, Yina; Lu, Zhiwen; Fang, Yibin; Zhao, Kaijun; Huang, Qinghai (Frontiers in Neurology, 2022)
Background and purpose Treatment of blood blister-like aneurysms (BBAs) has been a significant challenge mainly due to their high recurrence rate even after stent-assisted coiling (SAC) embolization. This study aims to evaluate the safety and efficacy of treating recurrent BBAs after SAC with a flow diverter (FD). Methods A retrospective series of patients with recurrent BBAs who underwent the retreatment with the FD from June 2018 to December 2021 was included to analyze perioperative safety and immediate postoperative and follow-up outcomes. Results The study enrolled 13 patients with recurrent BBAs previously treated with SAC. Within previous stents, an FD was deployed for retreatment, including eight Tubridge FDs and five PEDs. The time interval between initial treatment and FD implantation was 14–90 days. A total of 11 cases were treated with a single FD alone; two cases were treated with further endovascular coiling embolization, followed by FD implantation. The angiographic follow-up (6–12 months) was available in 12 patients, and all 12 recurrent BBAs were completely occluded. No perioperative complication was detected, and no rebleeding was found during the clinical follow-up (6–36 months). Conclusion The use of the FD to manage recurrent BBAs after SAC is technically feasible, safe, and effective. The key to the success of the procedure is to ensure that the FD stent is fully open and has good apposition with the previously implanted stent.